The chromosome-level holly (Ilex latifolia) genome reveals key enzymes in triterpenoid saponin biosynthesis and fruit color change - Xu, Ke-Wang; Wei, Xue-Fen; Lin, Chen-Xue; Zhang, Min; Zhang, Qiang; Zhou, Peng; Fang, Yan-Ming; Xue, Jia-Yu; Duan, Yi-Fan (Frontiers in Plant Science, 2022)
The Ilex L. (hollies) genus of Aquifoliaceae has been widely used in beverage and medicine production and as ornamentals. Here, we assembled a chromosome-level genome of Ilex latifolia, which is the raw material for making Kudingcha and used as decorative red berries. Phylogenomic analysis recovered I. latifolia as the first diverging lineage of campanulids. Two rounds of whole-genome duplications (WGDs) were identified and should be shared by all hollies. Through the combination of comparative genomics, phylogenetics, differential expression and co-expression analyses, we screened candidate genes involved in the biosynthesis of pentacyclic triterpenoid saponins in I. latifolia. Three CYP450 genes are likely to play important roles in pentacyclic triterpenoid saponins biosynthesis, and other candidate genes with similar expressional patterns to these three CYP450 genes are also identified, possibly also involved in this biosynthetic pathway. In addition, we identified genes in the biosynthesis of pelargonidin and cyanidin and observed differential expression of key enzymes in green and red fruit pericarps, suggesting an association between pelargonidin and cyanidin biosynthesis and fruit pericarp colour change. Altogether, this study elucidated the molecular basis of the medicinal and ornamental value of I. latifolia, providing a data basis and promising clues for further applications.